СОВЕРШЕНСТВОВАНИЕ СИСТЕМ УПРАВЛЕНИЯ – ФАКТОР ИННОВАЦИОННОГО РАЗВИТИЯ КОМПАНИЙ НЕФТЕГАЗОВОЙ ОТРАСЛИ - Новожилова, О Ю (Journal of Economic Research & Business Administration, 2015)
Nowadays management system is one of the most important mechanism of market economy. Management system is a mechanism of producing and realization of balanced solutions at all management's levels.